Case report: Endovascular stent-graft repair of aortic penetrating trauma, literature review, and case report - Bayona, Juan Gabriel; Rey Chaves, Carlos Eduardo; Hernández Rodríguez, Oscar Geovanny; Barón, Vladimir; Fajardo, Ernesto; Posada, Eduardo (Frontiers in Surgery, 2023)
Penetrating aortic injuries are infrequent. Its incidence is unknown because most patients die of hemorrhage even before they receive adequate treatment. Aortic wounds generally require conventional thoracotomy/laparotomy repair and are related to high mortality rates. Recently with the advent of endovascular techniques, most authors prefer endovascular management when feasible due to better (still poor) outcomes. The short- and mid-term results of immediate endovascular repair of traumatic aortic injuries are promising, especially when compared with open surgical treatment, indicating that endovascular therapy is preferable in patients with multi-trauma and traumatic ruptures of the thoracic aorta. Here we present the diagnosis and treatment of a 30 years-old male patient with multiple traumatic stab wounds, including anterior aortic laceration with a grade II aortic lesion successfully managed with an endovascular stent graft.